Carbon Aerogels Preparation With Kaolin addition. Issue 1 (September 2020) - Xu, Yuelong; Ren, Bin; Liu, Zhenfa
Abstract: Wet gels (WGs) have been obtained from the polymerization of phloroglucinol (P), resorcinol (R) and formaldehyde (F) using sodium carbonate (C) as catalyst with kaolin (KL) addition. Carbon aerogels (CAs) have been gotten through the carbonization of WGs. The porous texture properties of as - prepared samples are investigated using the surface-area analyzer. The crystal structure of CAs are studied by X-ray diffraction (XRD) and the degree of graphitization are obtained through a Raman spectrometer. Meanwhile scanning electron microscopy (SEM) are executed to observe the morphology of different samples. When the addition of 5 wt%, the samples exhibit the high specific surface area (SSA), up to 855m 2 g –1, with a concentrated pore size disdribution (PSD) of 30 nm.